Foregrounding endangered languages: engaging in change through language research / Stefanie Shamila Pillai - Pillai, Stefanie Shamila (Akademi Pengajian Bahasa, 2021)
It is estimated that almost 80% of languages in Malaysia are considered to be under threat. These include indigenous languages and creoles. Whilst there has been considerable research on Malaysia languages, including endangered languages, the main output tends to be in the form of academic publications. Given the importance of language for (i) communication; (ii) creating a sense of identity; (iii) information and knowledge transfer; and (iv) promoting sustainable development, how can language researchers make a difference where endangered languages are concerned? This is the main question that will be addressed in this talk, which will look at ways in which language researchers can foreground endangered languages. This could be through creating awareness of the existences of these languages and reducing negative or stereotypical views to developing creative opportunities to use and learn a language.